Prevent and manage high blood pressure using theory-based comprehensive nonpharmacological approaches - Wang, Yanli (My University, 2024)
High blood pressure (HBP), also known as hypertension (HTN), is a major health problem worldwide. The prevalence of HTN is a public health concern because it increases the risk for cardiovascular diseases worldwide. Primary prevention in the general population to prevent the risk of HTN and associated complications later in life is beneficial. Proper management in the hypertensive population could substantially reduce healthcare costs and improve quality of life. We conducted focus groups and one-on-one interviews to explore understanding, perceptions, and knowledge among adults on how to prevent and manage hypertension using nonpharmacological approaches and to identify nutrition education gaps for educational interventions. Our qualitative study revealed four underlying themes, which set the tone for education needs and knowledge gaps for educational interventions. The four underlying themes that emerged from the qualitative study were: (1) HTN and associated risk factors, (2) underestimated HTN complications, especially organ damage caused by HTN, (3) nutrition and HTN, and (4) integration of nonpharmacological approaches as part of a healthy lifestyle. The qualitative study provides a strong basis for developing effective nutrition education programs to prevent and manage HTN in adults. A randomized controlled trial was applied to investigate the effects of a four-week educational intervention on knowledge, perceptions, and behavior change in preventing and managing HBP among adults based on the Protection Motivation Theory (PMT) as a theoretical framework. Significant differences were observed between control and intervention groups in knowledge level (p=0.04), perceived severity (p=0.00), and response efficacy (p=0.01) after controlling for pre-survey data. Fruit and vegetable consumption increased compared to the baseline but was still below the dietary recommendation. Dietary potassium consumption increased in the intervention group compared to the control group. No significant difference was observed between the control and intervention groups in quality of life after controlling for pre-survey data. The findings of the study indicated that a short-term educational intervention promoting nonpharmacological approaches had positive effects on HBP prevention and management. Our study underscores the potential of educational interventions using PMT as a theoretical framework in the short-term prevention and management of HBP among adults. By intensively focusing on nonpharmaceutical approaches, we significantly enhanced knowledge, perceived severity, response efficacy, and protection motivation. Moreover, our findings demonstrate that a brief educational intervention promoting nonpharmacological approaches can effectively induce behavior change in HTN prevention and management.
Keywords: Hypertension; High blood pressure; Nonpharmacological approach; Lifestyle